2020
DOI: 10.3390/met10060806
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analysis of Friction Stir Butt Welded Al-Mg-Sc-Zr Alloy Heavy Gauge Sheets

Abstract: Friction stir welding (FSW) on a heavy gauge sheet of a hereditary fine-grained Al-Mg-Sc-Zr alloy was carried out to study the specifics of plasticized metal flow and microstructural evolution in different sections and zones of the joint. It was found that the stir zone (SZ) macrostructure may contain either a single or many nugget zones depending on the metal sheet thickness and the seam length. The effect of grain kinking in a thermomechanically affected zone (TMAZ) under pressure from the stir zone metal wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
19
0
3
Order By: Relevance
“…The authors of [25] also observed the earlier mentioned formation of complex flows of the alloy along the contour of the tool motion accompanied by the generation of a complexly organized multi-nugget stir zone with small separate vortex zones.…”
Section: Discussionmentioning
confidence: 71%
“…The authors of [25] also observed the earlier mentioned formation of complex flows of the alloy along the contour of the tool motion accompanied by the generation of a complexly organized multi-nugget stir zone with small separate vortex zones.…”
Section: Discussionmentioning
confidence: 71%
“…Adhesion-assisted transfer mechanism was proposed earlier for FSW [23], being potentially used to explain structural evolution of the CuZn37/AA5056 SZ. Adhesion of plasticized metal to the FSP/FSW tool plays the main role in layer-by-layer formation of the FSW weld joint.…”
Section: Discussionmentioning
confidence: 96%
“…Let us note that in fact FSW and FSP on dissimilar metals share the same structural evolution processes and therefore can be described using the same terms. In this connection, it is desirable to obtaining fine IMC particles evenly distributed in a stir zone, i.e., effective stirring is desirable, which is often prevented by strong adhesion between the stirred material and FSW tool [23]. Introduction of a low-melting element such as zinc would improve the intermixing and distribution of IMC.…”
Section: Introductionmentioning
confidence: 99%
“…В результате проведенных исследований были выявлены особенности структуры зоны перемешивания, где происходит выдавливание металла шва в зоне входа инструмента. Было подтверждено, что в процессе сварки происходит адгезионное взаимодействие инструмента и свариваемого материала с дальнейшим его послойным переносом, как это было показано в ранее проведенных работах на сплаве системы Al-Mg-Sc [3], однако, с некоторыми отличиями, ввиду использования разных материалов исследования. Проведенные механические испытания образцов показали, что их деформация происходит с ярко выраженным эффектом Портевена-Ле Шателье, при этом было выявлено, что подобранные параметры для сварки соединений из сплава АМг5 позволяют достичь высокого показателя предела прочности сварного соединения при испытаниях на статическое растяжение.…”
Section: Doi: 1017223/978-5-907442-03-0-2021-227 различия в структуре и механических свойствах материала в разных направлениях полученногunclassified